Preparation process of conductive film

In the conductive film preparation process, nano silver wires are dispersed in an organic volatile solvent and a conductive film is formed on the plastic film by using a scraping method, the problem of difficulty in preparing flexible transparent conductive films in the prior art is solved, and high voltage resistance, printable and high sensitivity conductive film preparation is achieved.

CN119852030APending Publication Date: 2025-04-18JIANGSU TELILAN COATING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510047362.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

It is difficult to prepare large-area conductive films with good flexibility and transparency, especially when maintaining conductive properties.

Method used

By dispersing the nano-silver wires in an organic volatile solvent, stirring evenly, the dispersion liquid is evenly applied on the plastic film substrate by scraping and baking and drying to form a conductive film. The process includes specific nanosilver mitoparticle size and length designs, combining appropriate plastic films and organic volatile solvent ratios to ensure the integrity and stability of the conductive network.

Benefits of technology

It has achieved the preparation of flexible tensile conductive films with high voltage resistance characteristics, printability, high conductivity, high sensitivity and wide strain range, which is suitable for the field of flexible wearable electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852030A_ABST
    Figure CN119852030A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation process of a conductive thin film, which comprises the following steps of: dispersing silver nanowires in an organic volatile solvent, and uniformly stirring to obtain dispersion liquid; uniformly coating a plastic film substrate with the dispersion liquid through a blade coating method, baking at 115-125 DEG C for 2-3 minutes for drying treatment, and removing the organic volatile solvent to form a conductive film; wherein the conductive film comprises the following components in parts by mass: 80-100 parts of a plastic film, 5-10 parts of nano silver wires and 90-95 parts of an organic volatile solvent. Through specific design of the particle size and functional groups of the silver nanowires, the particle size of the silver nanowires is 20-30 nm, the length of the silver nanowires is larger than 10 [mu] m, the length-diameter ratio of the fibrous conductive filler is large, a formed conductive network is complete and stable, the conductive network is not prone to damage under the pressure effect, and therefore the good piezoresistive characteristic is achieved; the flexible stretchable conductive film which can be printed and is high in conductivity, high in sensitivity and wide in strain range can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive films, and in particular to a preparation process of a conductive film. Background Art

[0002] Conductive polymer composites are one of the most important functional electronic materials for achieving conductive interconnection of electronic components and making electronic devices lightweight and flexible.

[0003] In the past, ITO thin film has been used as a transparent conductive film in optoelectronic devices for more than 50 years. However, due to its poor flexibility, it is completely unsuitable for the preparation of flexible transparent conductive film materials.

[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention

[0005] In view of the deficiencies in the prior art, an embodiment of the present invention discloses a process for preparing a conductive film, so as to realize the preparation of a transparent conductive film with good flexibility.

[0006] The technical solution adopted by the present invention is as follows:

[0007] A preparation process of a conductive film comprises the following steps: dispersing nano silver wires in an organic volatile solvent, stirring evenly to obtain a dispersion; coating the dispersion evenly on a plastic film substrate by a scraping method, baking at 115-125°C for 2-3 minutes for drying treatment, removing the organic volatile solvent, and forming a conductive film; wherein the conductive film comprises the following components in parts by mass: 80-100 parts of plastic film, 5-10 parts of nano silver wires, and 90-95 parts of an organic volatile solvent.

[0008] A further technical solution is to use a mechanical stirrer to stir at a speed of 300 to 500 r / min for 25 to 35 minutes to form a uniform nano silver wire dispersion.

[0009] A further technical solution is that the plastic film is any one of a PVA film, a PET film and a PE film.

[0010] A further technical solution is that the organic volatile solvent is toluene.

[0011] A further technical solution is that the particle size of the nano silver wire is 20-30 nm and the length is greater than 10 μm.

[0012] A further technical solution is that the length of the silver nanowire is 15 to 20 μm.

[0013] A further technical solution is that the silver nanowire is prepared by any one of thermal reduction, chemical deposition, and one-step polymerization, and the structure of the silver nanowire is characterized by any one of an X-ray diffractometer, a scanning electron microscope, and a transmission electron microscope, and its morphology and state are monitored in real time.

[0014] The further technical solution is that the tensile strength of the conductive film is 15-50 MPa and the piezoresistance coefficient is 1.7*10 -5 ~1.9*10 -5 m 2 / N.

[0015] The beneficial effects of the embodiments of the present invention are as follows:

[0016] (I) The preparation process of the conductive film of the embodiment of the present invention is to specifically design the particle size of the nano silver wire, the functional group, etc., so that the particle size of the nano silver wire is designed to be 20-30 nm, the length is greater than 10 μm, the fibrous conductive filler has a large aspect ratio, and the conductive network formed is relatively complete and stable. The conductive network is not easily destroyed under pressure, so it has good piezoresistive properties, and can produce a printable, high-conductivity, high-sensitivity and wide-strain range flexible and stretchable conductive film.

[0017] (ii) Furthermore, the nano silver wires are dispersed in an organic volatile solvent and stirred evenly to obtain a dispersion, and the dispersion is evenly coated on a plastic film substrate by a scraping method. The plastic film substrate has good flexibility and good deformation resistance. The dispersion is evenly coated and is not easy to break or deform during the stretching process. It is suitable for the field of flexible wearable electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The present invention is a flow chart of the process for preparing the conductive film. DETAILED DESCRIPTION

[0019] The specific implementation of the present invention will be described below in conjunction with the accompanying drawings.

[0020] In order to make the purpose, technical scheme and advantages of the present invention clearer, the device proposed by the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments. According to the following description, the advantages and features of the present invention will be clearer. It should be noted that the accompanying drawings adopt a very simplified form and use non-precise proportions, which are only used to conveniently and clearly assist in explaining the purpose of the embodiments of the present invention. In order to make the purpose, features and advantages of the present invention more obvious and easy to understand, please refer to the accompanying drawings. It should be noted that the structure, proportion, size, etc. illustrated by the accompanying drawings of this specification are only used to match the content disclosed in the specification for people familiar with this technology to understand and read, and are not used to limit the limiting conditions for the implementation of the present invention, so they have no technical substantive significance. Any modification of the structure, change of the proportional relationship or adjustment of the size, without affecting the effect that the present invention can produce and the purpose that can be achieved, should still fall within the scope of the technical content disclosed by the present invention.

[0021] First embodiment:

[0022] A process for preparing a conductive film comprises the following steps:

[0023] Step S1, dispersing the silver nanowires in an organic volatile solvent and stirring the mixture to obtain a dispersion.

[0024] Specifically, a mechanical stirrer is used for stirring at a speed of 400 r / min for 30 minutes to form a uniform nanosilver wire dispersion. The particle size of the nanosilver wire is 20 nm and the length is 20 μm. The organic volatile solvent is toluene. The nanosilver wire is prepared by a hydrothermal method, and the structure of the silver nanowire is characterized by an X-ray diffractometer, and its morphology and state are monitored in real time. In the XRD spectrum, diffraction peaks of the nanosilver wire can be observed, and these peaks correspond to specific crystal planes of silver.

[0025] Step S2, coating the dispersion evenly on the plastic film substrate by a doctor blade method, baking at 120° C. for 2.5 minutes for drying to remove the organic volatile solvent and form a conductive film.

[0026] The conductive film includes the following components in parts by weight: 90 parts of PVA film, 7 parts of nano silver wires, and 92 parts of toluene.

[0027] Second embodiment:

[0028] A process for preparing a conductive film comprises the following steps:

[0029] Step S1, dispersing the silver nanowires in an organic volatile solvent and stirring the mixture to obtain a dispersion.

[0030] Specifically, a mechanical stirrer is used for stirring at a speed of 300 r / min for 35 minutes to form a uniform nanosilver wire dispersion. The particle size of the nanosilver wire is 30 nm and the length is 15 μm. The organic volatile solvent is toluene. The nanosilver wire is prepared by a chemical deposition method, and the structure of the silver nanowire is characterized by a scanning electron microscope, and its morphology and state are monitored in real time. TEM images can intuitively display the morphology, size and distribution of the nanosilver wire.

[0031] Step S2, coating the dispersion evenly on the plastic film substrate by a doctor blade method, baking at 115° C. for 3 minutes for drying to remove the organic volatile solvent and form a conductive film.

[0032] The conductive film includes the following components in parts by weight: 80 parts of PVA film, 5 parts of nano silver wires, and 95 parts of toluene.

[0033] Third embodiment:

[0034] A process for preparing a conductive film comprises the following steps:

[0035] Step S1, dispersing the silver nanowires in an organic volatile solvent and stirring the mixture to obtain a dispersion.

[0036] Specifically, a mechanical stirrer is used for stirring at a speed of 500 r / min for 25 minutes to form a uniform nanosilver wire dispersion. The particle size of the nanosilver wire is 20 nm and the length is 15 μm. The organic volatile solvent is toluene. The nanosilver wire is prepared by a chemical reduction method, and the structure of the silver nanowire is characterized by a transmission electron microscope, and its morphology and state are monitored in real time. The SEM scanning electron microscope can image the appearance of the nanosilver wire and observe the dispersion state.

[0037] Step S2, coating the dispersion evenly on the plastic film substrate by a doctor blade method, baking at 125° C. for 2 minutes for drying to remove the organic volatile solvent and form a conductive film.

[0038] The conductive film includes the following components in parts by weight: 100 parts of PET film, 10 parts of nano silver wires, and 90 parts of toluene.

[0039] Fourth embodiment:

[0040] A process for preparing a conductive film comprises the following steps:

[0041] Step S1, dispersing the silver nanowires in an organic volatile solvent and stirring the mixture to obtain a dispersion.

[0042] Specifically, a mechanical stirrer is used to stir at a speed of 300 to 500 r / min for 30 minutes to form a uniform nanosilver wire dispersion. The particle size of the nanosilver wire is 20 nm and the length is 15 μm. The organic volatile solvent is toluene. The nanosilver wire is prepared by a hydrothermal method, and the structure of the silver nanowire is characterized by a transmission electron microscope, and its morphology and state are monitored in real time. The SEM scanning electron microscope can image the appearance of the nanosilver wire and observe the dispersion state.

[0043] Step S2, coating the dispersion evenly on the plastic film substrate by a doctor blade method, baking at 120° C. for 2 minutes for drying to remove the organic volatile solvent and form a conductive film.

[0044] The conductive film includes the following components in parts by weight: 82 parts of PE film, 6 parts of nano silver wires, and 95 parts of toluene.

[0045] The first comparison:

[0046] The nano silver wires are replaced with nano silver particles, the particle size of the nano silver particles is 800 nm, and the rest is the same as the first embodiment.

[0047] Test example

[0048] The conductive films prepared in the first embodiment, the second embodiment, the third embodiment and the first comparative example were subjected to performance tests. The test results are shown in Table 1.

[0049] Table 1

[0050] Tensile strength(MPa) <![CDATA[Piezo-resistive coefficient (m 2 / N)]]> First embodiment 35 <![CDATA[1.2×10 -6 ]]> Second embodiment 35 <![CDATA[1.9×10 -5 ]]> Third embodiment 50 <![CDATA[1.7×10 -5 ]]> Fourth embodiment 15 <![CDATA[1.7×10 -5 ]]> The first comparison 10 <![CDATA[1.7×10 -2 ]]>

[0051] Detection method:

[0052] Tensile strength: According to ASTM D882 standard. During the test, the conductive film needs to be clamped in the fixture of the testing machine and a certain tensile speed is applied to record the stress-strain curve of the film during the stretching process, as well as the maximum tensile force and elongation when the film breaks.

[0053] Piezoresistance coefficient: The piezoresistance coefficient is calculated by applying mechanical stress to the conductive film using the four-point electrode method and observing the change in current through the four electrodes. The change in resistivity ρ of the conductive film Dρ is proportional to the strain ε, so the relative change in resistivity is proportional to the stress:

[0054] Dρ / ρ=p·ε;

[0055] Where p is the piezoresistance coefficient.

[0056] As can be seen from the table, the conductive chain of particle-shaped conductive fillers is easy to slip under pressure, which is easy to destroy the existing conductive network distribution, thus affecting the piezoresistive performance. However, the fibrous conductive fillers have a large aspect ratio, and the conductive network they form is relatively complete and stable. The conductive network is not easily destroyed under pressure, so they have better piezoresistive properties and can be used to produce printable, high-conductivity, high-sensitivity and wide-strain-range flexible and stretchable conductive films.

[0057] Specifically, the printability is reflected in the use of copper or gold to form a metal film by depositing it on a flexible or superelastic substrate through adhesive bonding, printing, sputtering, electron evaporation, etc. At the same time, the formula and process of the present invention can achieve a balance between high conductivity, high sensitivity and a wide strain range, maintaining the integrity of the material structure and morphology at a large strain, and producing a certain amount of sudden structural changes at a small strain.

[0058] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0059] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A process for preparing a conductive film, characterized in that: The following steps are involved: Dispersing the silver nanowires in an organic volatile solvent and stirring the mixture to obtain a dispersion; The dispersion is evenly coated on a plastic film substrate by a doctor blade method, and then dried at 115 to 125° C. for 2 to 3 minutes to remove the organic volatile solvent and form a conductive film. Wherein, the conductive film comprises the following components in parts by weight: 80-100 parts of plastic film, 5-10 parts of nano silver wire, and 90-95 parts of organic volatile solvent.

2. The process for preparing the conductive film according to claim 1, characterized in that: A mechanical stirrer is used for stirring at a speed of 300 to 500 r / min for 25 to 35 minutes to form a uniform nano silver wire dispersion.

3. The process for preparing the conductive film according to claim 1, characterized in that: The plastic film is any one of a PVA film, a PET film and a PE film.

4. The process for preparing the conductive film according to claim 1, characterized in that: The organic volatile solvent is toluene.

5. The process for preparing the conductive film according to claim 1, characterized in that: The particle size of the nano silver wire is 20-30 nm, and the length is greater than 10 μm.

6. The process for preparing the conductive film according to claim 5, characterized in that: The length of the silver nanowire is 15 to 20 μm.

7. The process for preparing the conductive film according to claim 5, characterized in that: The silver nanowires are prepared by any one of thermal reduction, chemical deposition and one-step polymerization, and the structure of the silver nanowires is characterized by any one of an X-ray diffractometer, a scanning electron microscope and a transmission electron microscope, and the morphology and state of the silver nanowires are monitored in real time.

8. The process for preparing a conductive film according to claim 1, characterized in that: The tensile strength of the conductive film is 15-50 MPa and the piezoresistance coefficient is 1.7*10 -5 ~1.9*10 -5 m 2 / N.